2019
DOI: 10.1038/s41558-019-0540-7
|View full text |Cite
|
Sign up to set email alerts
|

How contemporary bioclimatic and human controls change global fire regimes

Abstract: Fires play an important role in ecosystem dynamics. Long-term controls on global burned area include fuel continuity and moisture, with ignitions and human activity becoming dominant in specific ecosystems. Changes in fuel continuity and moisture are the main drivers of changes of fire globally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
162
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(168 citation statements)
references
References 55 publications
5
162
0
1
Order By: Relevance
“…Our results are generally consistent with Meyn et al (2007), who found that decreasing fuel moisture (increasing dryness) was important in promoting fire in a wide range of forests and other biomass-rich, rarely dry vegetation types, and Krawchuk and Moritz (2011), who found that mesic areas where biomass is relatively abundant experienced more fire activity as fuels dried, as indexed by soil moisture. Kelley et al (2019) identified some forests (though not all) where fire regimes have shifted consistent with this relationship between fire activity and fuel moisture trends.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Our results are generally consistent with Meyn et al (2007), who found that decreasing fuel moisture (increasing dryness) was important in promoting fire in a wide range of forests and other biomass-rich, rarely dry vegetation types, and Krawchuk and Moritz (2011), who found that mesic areas where biomass is relatively abundant experienced more fire activity as fuels dried, as indexed by soil moisture. Kelley et al (2019) identified some forests (though not all) where fire regimes have shifted consistent with this relationship between fire activity and fuel moisture trends.…”
Section: Discussionmentioning
confidence: 59%
“…In this modelling study we did not attempt to explain seasonal or inter-annual variability in fire activity in terms of corresponding temporal variability in each fundamental determinant of fire (Abatzoglou et al, 2018;Kelley et al, 2019). Nevertheless, because we used multi-decadal fire and predictor records, the relationships implicitly reflected this variation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and 265 systematic evaluation of their performance is ongoing as part of the fire modelling intercomparison project (FIREMIP) (Hantson et al, 2016;Rabin et al, 2017;Teckentrup et al, 2019;Forkel et al, 2019). Our hydroclimatic model is conceptually similar to a global model proposed by Kelley et al (2019) that predicts burned area as a function of four limitations (i.e. fuel continuity, fuel moisture, potential ignitions and a suppression index).…”
Section: Discussion 255mentioning
confidence: 99%
“…Today, roughly 3% of the Earth's surface burns annually (van der Werf et al 2017). Current fire regimes are greatly influenced by humans through ignition sources, suppression, and changes in land cover and fuels (Bistinas et al 2013, Kelley et al 2019. Fire regimes are also rapidly changing, a function of changing climate patterns, extreme weather, land use, human population, and vegetation distributions (Jolly et al 2015, Andela et al 2017, Veraverbeke et al 2017.…”
Section: Introductionmentioning
confidence: 99%